Pd-Catalyzed regio- and stereoselective allylic substitution of vinylethylene carbonates with 1, 2, 4-triazoles. Issue 33 (26th July 2022) - Khan, Sardaraz; Shah, Babar Hussain; Zhao, Can; Zhang, Yong Jian
Abstract : Pd-Catalyzed allylic substitution of vinylethylene carbonates with 1, 2, 4-triazoles has been developed to produce N 1 -allylated 1, 2, 4-triazoles in high yields with excellent regio- and stereoselectivities. Abstract : N 1 -Substituted 1, 2, 4-triazoles are ubiquitous skeletons in medicinal agents, agrochemicals, and organic materials. Herein, an efficient and practical method for the synthesis of N 1 -allylated 1, 2, 4-triazoles via Pd-catalyzed allylic substitution of vinylethylene carbonates (VECs) with 1, 2, 4-triazoles has been developed. By using a catalyst generated in situ from Pd2 (dba)3 ·CHCl3 and DPPE under mild conditions, the process allows rapid access to N 1 -allylated 1, 2, 4-triazoles bearing diverse functionalities in high yields with excellent N 1 -selectivities, linear-selectivities, and Z -stereoselectivities.